On some limit properties of functions with nonvanishing divided differences - Kiriyatzkii, Eduard; Kirjackis, J. (Mathematical Modelling and Analysis, 2009)
In present article the sequence of holomorphic in region D functions Fn (z) which have exactly n zeros in this region is considered. The limit properties of the sequence Fn (z), of functions with non‐vanishing divided differences of n‐th order are investigated. One interpolation property, connected with Chebyshev systems is considered. First published online: 14 Oct 2010